"Melioidosis in Antioquia, Colombia: an emerging or endemic disease? A cases series". (August 2015) - Montúfar, F.E.; Ochoa, J.E.; Ortega, H.; Franco, L.; Montúfar, M.C.; Monsalve, A.; Jaramillo, C.; Zapata, M.
Highlights: Melioidosis is endemic in Asian countries and Australia. It is a disease with different clinical presentations and diagnosis is difficult. There are few descriptions in the Americas despite the presence of the same ecological conditions as in endemic areas. Is melioidosis in the Americas really endemic? Summary: Background: Melioidosis is endemic in Malaysia, the southwest of Thailand, and northern Australia. The incidence in Thailand is 4.4/1 000 000 inhabitants, where it causes 19% of community-acquired pneumonia (CAP) and 20% of bacteremic pneumonia, and the mortality is 50%. Sporadic cases have been described in Central and South America. The objective of this study was to describe the clinical and epidemiological features and ecological characteristics of melioidosis in Antioquia, Colombia. Methods: This is a case series description. Results: Seven cases were identified. Burkholderia pseudomallei was isolated from peripheral blood, pleural fluid, and urine and was identified by the automated system VITEK 2 (bioMérieux) and API 20NE biochemical kit. Five of the cases had a bacteremic form with shock and pulmonary compromise and two of these patients died. The non-bacteremic melioidosis cases had genitourinary, abdominal, and osteoarticular compromise. All patients had comorbidities and lived in rural hot and humid areas in the west central region of Colombia (Antioquia). Diabetes mellitus, renal insufficiency, and other chronic diseases are important risk factors for the development of severe forms. Conclusions: The cases presented here are similar to those occurring in endemic areas regarding comorbidity, risk factors, clinical presentation, and environmental conditions. It is necessary to establish whether melioidosis is an endemic and under-diagnosed disease or an emerging disease in Colombia.